Harnessing the potential of older workers through relationships at work: Social support, feedback, and performance - Marques, T.; Ramos, S.; Patient, D.; Bobocel, D. R. (Work, Aging and Retirement, 2024)
With the aging of the global workforce, it is crucial to deepen our understanding of how to keep older workers healthy, motivated, and productive. In this research, we integrate job design with socioemotional selectivity theory to propose that social job characteristics relate to employee performance differently for older and younger workers. Specifically, in a 3-wave survey (N = 454), we tested employee age as a moderator of the relationships between receiving social support and feedback at work, and performance, as well as giving social support and feedback at work, and performance. The results showed that, in general, both receiving and giving social support and feedback are associated more strongly with the performance of older than younger workers. The findings provide important theoretical implications for the study of aging and work; they also offer practical applications for creating workplaces in which older workers can reap the benefits of social relationships to remain productive.